2005
DOI: 10.1080/10196780500209010
|View full text |Cite
|
Sign up to set email alerts
|

Untangling the Antecedents and Covariates of E‐Commerce Trust: Institutional Trust vs. Knowledge‐Based Trust

Abstract: A b s t r a c t Through experimentation, we establish a causal relationship between structural assurance and both vendor trustworthiness (knowledge-based trust) and technology trustworthiness (institution-based trust). We expand the definitions of structural assurance and institution-based trust to include the element of security measures employed by the marketplace technology. Situational normality demonstrates a causal relationship with technology trustworthiness, and with vendor trustworthiness, the latter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 30 publications
(100 reference statements)
1
22
1
Order By: Relevance
“…SA can be the most significant predictor for a web vendor's perceived trustworthiness, besides calculativebased beliefs, situational normality and familiarity (Gefen et al 2003). Wingreen and Baglione (2005) found that SA can increase both vendor trustworthiness and technology trustworthiness. In the context of online investing, investors' beliefs about the overall online investment environment and the protection from regulatory agencies have stronger influence on the perceived trustworthiness of the online broker than the perceived competence of the broker even after some of the influence of SA was channeled through perceived competence (Balasubramanian et al 2003).…”
Section: Literature Reviewmentioning
confidence: 97%
“…SA can be the most significant predictor for a web vendor's perceived trustworthiness, besides calculativebased beliefs, situational normality and familiarity (Gefen et al 2003). Wingreen and Baglione (2005) found that SA can increase both vendor trustworthiness and technology trustworthiness. In the context of online investing, investors' beliefs about the overall online investment environment and the protection from regulatory agencies have stronger influence on the perceived trustworthiness of the online broker than the perceived competence of the broker even after some of the influence of SA was channeled through perceived competence (Balasubramanian et al 2003).…”
Section: Literature Reviewmentioning
confidence: 97%
“…Cheung and Lee's measurement instrument has been widely published (2000a, b; 2001; 2002; 2003) and cited by authors in international peer-reviewed journals such as the Journal of Global Information Management (Corner et al, 2005), the Journal of E-Commerce in Organisations (Cheung et al, 2005), Electronic Markets (Wingreen and Baglione, 2005), the International Journal of Management (Parnell et al, 2003) and the International Journal of Electronic Commerce (Hampton-Sosa and Koufaris, 2005). The instrument has been previously applied in the United States (Borchers, 2001).…”
Section: R Connolly and F Bannistermentioning
confidence: 99%
“…Findings from a study carried out by [60] in U.S.A., Singapore, and China indicated that propensity to trust has a positive impact on consumer trust in electronic commerce. Similarly, the research conducted by [67] also suggested that propensity to trust positively affects online trust.…”
Section: Personality-based Trustmentioning
confidence: 99%
“…The factors were: online trust [22], [23], [31], [34], [40], [48], reputation [34], [40], [60], perceived security [10], [40], [61], [63], perceived privacy [10], [8], [64], [63], propensity to trust [10], [22], [48], [60], [67], third-party assurance [10], [23], familiarity [22], [23], [67], website quality [11], [14], [44], [48], brand [18], [68], and customer service [58].…”
Section: Research Frameworkmentioning
confidence: 99%